Złożenia w rosyjskim slangu młodzieżowym - Kubecka, Katarzyna (Studia Rossica Posnaniensia, 2018)
The article is devoted to compounds in Russian youth slang. The author proves that young people treat compounds as a basis for creative modifications and play with words by combining various parts of speech, different styles, languages in one in order to create humorous formations.